Features of Intraseasonal Variability Observed in the Upper-Layer Current in the Northern South China Sea - Xu, Wen; Shu, Yeqiang; Wang, Dongxiao; Chen, Ju; Wang, Jinghong; Xie, Qiang; Wang, Qiang; Liu, Danian; Zu, Tingting; He, Yunkai (Frontiers in Marine Science, 2021)
This study reveals the features of the strong intraseasonal variability (ISV) of the upper-layer current in the northern South China Sea (NSCS) based on four long-time mooring observations and altimeter data. The ISV of the upper-layer current in the NSCS consists of two dominant periods of 10-65 days and 65-110 days. The ISV with the period of 10-65 days is much strong in the Luzon Strait and decays rapidly westward along the slope. The ISV with the period of 65-110 days is relatively strong along the slope with two high cores at 115°E and 119°E, whereas it is weak in the Luzon Strait. The 10-65-day ISV can propagate directly from western Pacific into the NSCS for most of the time. However, due to its long wavelength, the 65-110-day ISV propagates into the NSCS indirectly, possibly similar to the wave diffraction phenomenon. The spatial differences between the two main frequency bands are primarily due to the baroclinic and barotropic instabilities. The spatial distribution of the upper-layer ISV is closely associated with the mesoscale eddy radius of the NSCS. The eddy radius is proportional to the strength of 65-110-day ISV but inversely proportional to the strength of 10-65-day ISV.